A Pressure‐Induced Inverse Order–Disorder Transition in Double Perovskites. (6th April 2020) - Deng, Zheng; Kang, Chang‐Jong; Croft, Mark; Li, Wenmin; Shen, Xi; Zhao, Jianfa; Yu, Richeng; Jin, Changqing; Kotliar, Gabriel; Liu, Sizhan; Tyson, Trevor A.; Tappero, Ryan; et al.
Abstract: Given the consensus that pressure improves cation ordering in most of known materials, a discovery of pressure‐induced disordering could require recognition of an order–disorder transition in solid‐state physics/chemistry and geophysics. Double perovskites Y2 CoIrO6 and Y2 CoRuO6 polymorphs synthesized at 0, 6, and 15 GPa show B‐site ordering, partial ordering, and disordering, respectively, accompanied by lattice compression and crystal structure alteration from monoclinic to orthorhombic symmetry. Correspondingly, the long‐range ferrimagnetic ordering in the B‐site ordered samples are gradually overwhelmed by B‐site disorder. Theoretical calculations suggest that unusual unit‐cell compressions under external pressures unexpectedly stabilize the disordered phases of Y2 CoIrO6 and Y2 CoRuO6 . Abstract : Double perovskites Y2 CoIrO6 and Y2 CoRuO6 show an increase of B ‐site disorder with increasing synthesis pressure. This pressure‐induced disorder is accompanied by lattice compression and structure alteration and the long‐range ferrimagnetic orderings gradually collapsed. Calculations suggest that unusual cell compressions under pressures unexpectedly stabilize the disordered phases.